Financial management practices of administrators of high-performing Christian schools in the National Capital Region - Santiago, Nerissa B. (2008)
This qualitative research aimed to describe the financial management practices of administrators of performing Christian schools in the National Capital Region. The researcher used survey questionnaire and interviews to gather the data. The study showed that the administrators practices are having proper organizational structures. They have: (1) proper accounting procedures, standards and appropriate accounting cycles in financial department; (2) efficient financial staff on internal control procedures; (3) checking procedures on internal and external auditing; (4) management of capital assets; (5) revenues and fund sources; (6) cost-control management; and (7) effective budget management and resource allocation practices.
Thesis (M.A. Educational Administration)--University of the Philippines, Diliman.
Keywords: School administrators -- Philippines -- National Capital Region; Church schools -- Philippines -- National Capital Region -- Finance; Church schools -- Philippines -- National Capital Region -- Administration; School management and organization -- Philippines -- National Capital Region